Tendencies of various brewery operation parameters - Szabó, Edina; Sipos, Péter (Acta Agraria Debreceniensis, 2015)
Beer is a very popular beverage which is the result of complex processes. Its quality and parameters are the outcomes of transformation of components from raw material. We tried to find out during our research how the parameters – the total polyphenol content, the colour and the total sugar content – of our self-brewed beers change during the brewing.